2004
DOI: 10.1038/sj.hdy.6800565
|View full text |Cite
|
Sign up to set email alerts
|

Cytogenetic mechanism and genetic consequences of thelytoky in the wasp Trichogramma cacoeciae

Abstract: In Hymenoptera, complete parthenogenesis, that is thelytoky, is a common phenomenon where virgin females produce only daughters. Thelytoky is often induced by bacteria of the genus Wolbachia, but can also be genetically determined by the insect itself, as in the genus Trichogramma where both forms exist. In order to compare these two forms of thelytoky, chromosome behaviour analysis in young eggs and genetic analysis of microsatellite markers were carried out in the wasp Trichogramma cacoeciae, where thelytoky… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
65
0
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 57 publications
(68 citation statements)
references
References 19 publications
2
65
0
1
Order By: Relevance
“…However, the mechanism of the Rickettsia-induced parthenogenesis described here maintains heterozygosity, and consequently takes away one of the barriers involved in the transition from sexual to thelytokous reproduction for species that commonly outbreed, such as most diplodiploid species. It is interesting to note that apomictic parthenogenesis is the most common form of parthenogenesis within diplodiploid arthropods (Suomalainen et al 1987) and has been found in some Hymenoptera where parthenogenesis is not associated with microbial infection ( Vavre et al 2004). Our results suggest that in the future we may detect the presence of parthenogenesis-inducing symbionts in diplodiploid species.…”
Section: Results (A) Allele Segregationsupporting
confidence: 58%
See 2 more Smart Citations
“…However, the mechanism of the Rickettsia-induced parthenogenesis described here maintains heterozygosity, and consequently takes away one of the barriers involved in the transition from sexual to thelytokous reproduction for species that commonly outbreed, such as most diplodiploid species. It is interesting to note that apomictic parthenogenesis is the most common form of parthenogenesis within diplodiploid arthropods (Suomalainen et al 1987) and has been found in some Hymenoptera where parthenogenesis is not associated with microbial infection ( Vavre et al 2004). Our results suggest that in the future we may detect the presence of parthenogenesis-inducing symbionts in diplodiploid species.…”
Section: Results (A) Allele Segregationsupporting
confidence: 58%
“…This cytological mechanism is similar to that of a non-bacteria-induced thelytoky in the parasitoid wasp Trichogramma cacoeciae and is also known as apomictic cloning ( figure 1a(ii); Vavre et al 2004). …”
mentioning
confidence: 71%
See 1 more Smart Citation
“…Third, when parthenogenesis-inducing endosymbionts have been found in a species, they are often assumed to occur in related parthenogenetic species, which is not necessarily true. Mechanisms underlying parthenogenesis can greatly differ between highly related species, as shown in Trichogramma (Vavre et al 2004) and Encarsia parasitoids wasps (Gokhman 2009) as well as Aptinothrips grass thrips (van der Kooi and Schwander 2014a), where parthenogenesis is caused by endosymbionts in some species, but via another mechanism in others. In conclusion, in 42% of the investigated haplodiploid species parthenogenesis is due to endosymbionts, but the actual frequency presumably is much lower.…”
Section: Endosymbiont-induced Parthenogenesis Is Proven To Occur In 4mentioning
confidence: 99%
“…Furthermore, a preliminary test of microsatellite loci amplification in a sample of parthenogenetic females from the Azores detected only one clone , which suggests that recombination does not take place and that asexual populations from the Azores probably arose from a single event. Absence of recombination has been found to occur in Bdelloid rotifers (Welch and Meselson, 2000), in the parthenogenetic wasp Trichogramma cacoeciae (Vavre et al, 2004) and in parthenogenetic oribatid mites (Schaefer et al, 2006). In addition, in thelytokous females of Apis mellifera capensis, recombination rates are lower than in sexually reproducing females of the same species.…”
Section: Parthenogenesis In Ischnura Hastatamentioning
confidence: 99%